Phylloplane Mycoflora of Colocasia at Different Growth Stages and their Antagonistic Effect on Colocasia Leaf Blight Pathogen in Vitro - Chakruno, P.; Banik, S. (International Journal of Bio-resource and Stress Management, 2015)
The phylloplane mycoflora study of colocasia at different growth stages resulted in isolation of an oomycete Phytophthora colocasiae and seven (7) fungal species viz., Cladosporium herbarum, Penicillium citrinum, Aspergillus niger isolate 1, Aspergillus niger isolate 2, Penicillium spp., Mucor hiemalis and Penicillium oxalicum. Phytophthora colocasiae, the leaf blight pathogen of colocasia and Penicillium citrinum were observed predominant throughout the growing season. Leaf washing method was followed for isolating phylloplane fungi from colocasia leaf using Martin’s Rose Bengal Agar as the cultivation media. Phytophthora colocasiae was observed with the highest mean number of colonies (26.60) during all the observations at different plant ages followed by P. citrinum (9.47), C. herbarum (3.27), M. hiemalis (0.47), A. niger isolate 1 (0.40), A. niger isolate 2 (0.13) and the lowest was observed for Penicillium spp. (0.07). However marked fluctuations were observed in the population of mycoflora on the leaf surface of colocasia with the days of interval which may be correlated to rainfall that was observed during the course of the investigation. Phylloplane fungal isolates were test against Phytophthora colocasiae the leaf blight pathogen of colocasia for their antagonistic properties using dual culture method. Mucor hiemalis (50.57) was found to have fast growth and over grow the pathogen colony completely five days after inoculation, where as Cladosporium herbarum (8.37) was observed to record the lowest inhibition of the leaf blight pathogen.